2021
DOI: 10.3390/children8050322
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Drug and Device Therapies for Pediatric Heart Failure Patients: Potential Lessons from Adult Trials

Abstract: This review discusses the potential drug and device therapies for pediatric heart failure (HF) due to reduced systolic function. It is important to realize that most drugs that are used in pediatric HF are extrapolated from adult cardiology practices or consensus guidelines based on expert opinion rather than on evidence from controlled clinical trials. It is difficult to conclude whether the drugs that are well established in adult HF trials are also beneficial for children because of tremendous heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
0
10
0
1
Order By: Relevance
“…Because the causes of heart failure in children differs significantly from that in adults, extrapolation of treatment modalities from adults to children is not ideal especially with the varying pharmacokinetics and pharmacodynamics of drugs observed from birth through adolescence. 2 In this study, use of antibiotics played a major role because of the predominance of acute lower respiratory tract infections and sepsis as causes of heart failure.…”
Section: -12mentioning
confidence: 98%
See 1 more Smart Citation
“…Because the causes of heart failure in children differs significantly from that in adults, extrapolation of treatment modalities from adults to children is not ideal especially with the varying pharmacokinetics and pharmacodynamics of drugs observed from birth through adolescence. 2 In this study, use of antibiotics played a major role because of the predominance of acute lower respiratory tract infections and sepsis as causes of heart failure.…”
Section: -12mentioning
confidence: 98%
“…1 It is a subject that although widely studied, continues to present challenges in management especially in children with difficulties still existing in drug therapy because of the variation that exists not only in drug pharmacokinetics and pharmacodynamics as children grow from birth to adolescence but also in the causes of heart failure in children. 2 In Nigeria, the prevalence of paediatric heart failure is known to vary widely with rates ranging between 3%-15.5% with most of the studies being hospital based. [3][4][5][6][7][8] Globally, the incidence and prevalence of heart failure is difficult to ascertain owing to the lack of a consensus definition for heart failure however, a recent study by Shaddy et al gave incidence rates ranging between 0.87/100,000 (UK and Ireland), 7.4/100,000 (Taiwan), and 83.3/100,000 (Spain).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the use of ACEIs was approved for the treatment of pediatric heart failure, regardless of etiology [46]. However, its effects have not been thoroughly studied [50]. To date, there is a class I recommendation for patients with left ventricular dysfunction for the use of ACEIs, as well as a class IIa recommendation for asymptomatic patients [14] Some studies have shown that adults with heart failure and children with dilated cardiomyopathy or systolic ventricular function treated with ACEIs had better survival at a one-and two-year follow-up compared with those treated with digoxin and potassium diuretics, such as spironolactone (Sections 2.5.3 and 2.3.2, respectively) [13,14].…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…In 2013, the use of ACEIs was approved for the treatment of pediatric heart failure, regardless of etiology [ 46 ]. However, its effects have not been thoroughly studied [ 50 ]. To date, there is a class I recommendation for patients with left ventricular dysfunction for the use of ACEIs, as well as a class IIa recommendation for asymptomatic patients [ 14 ].…”
Section: Drugs For Chd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation